2019
DOI: 10.1021/acsmedchemlett.9b00188
|View full text |Cite
|
Sign up to set email alerts
|

Truncated Itraconazole Analogues Exhibiting Potent Anti-Hedgehog Activity and Improved Drug-like Properties

Abstract: We conducted a structure−activity relationship study to explore simplified analogues of the itraconazole (ITZ) scaffold for their ability to inhibit the hedgehog (Hh) signaling pathway. These analogues were based on exploring the effects of chemical modifications to the linker and triazolone/side chain region of ITZ. Analogue 11 was identified as the most potent compound in our first generation, with an IC 50 value of 81 nM in a murine Hh-dependent basal cell carcinoma. Metabolic identification studies led us … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Compounds 3q and 3r, containing a crucial N-phenylpiperizinyl moiety that has been used in drug molecules (see ESI, Fig. S1), 50,51 were also synthesized through this approach. Remarkably, it was also possible to prepare 1,4-dipyrrolidinylbenzenes (2a-d) in high selectivities from DOH and pyrrolidines simply by switching the acid catalyst to 2.0 equivalents of HOAc.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 3q and 3r, containing a crucial N-phenylpiperizinyl moiety that has been used in drug molecules (see ESI, Fig. S1), 50,51 were also synthesized through this approach. Remarkably, it was also possible to prepare 1,4-dipyrrolidinylbenzenes (2a-d) in high selectivities from DOH and pyrrolidines simply by switching the acid catalyst to 2.0 equivalents of HOAc.…”
Section: Resultsmentioning
confidence: 99%
“…Excluding compounds 20 , 26 , 31 and 35 , for all synthetized compounds registered CAS numbers have been already assigned. However, their synthetic procedures, chemical properties and structural characterization are not available in literature, except for derivatives 2 , 6 , 30 , and 32 [33–35] …”
Section: Methodsmentioning
confidence: 99%
“…However, their synthetic procedures, chemical properties and structural characterization are not available in literature, except for derivatives 2, 6, 30, and 32. [33][34][35] 3.03 (m, 2H, CH 2 ), 3.23 (t, J = 5.2 Hz, 2H, CH 2 ), 3.76 (m, 2H, CH 2 ), 6.65 (d, J = 8.7 Hz, 2H, ArH, H-2" and H-6"), 6.80 (d, J = 8.7 Hz, 2H, ArH, H-3" and H-5"), 7.37 (m, 2H, ArH, H-4' and H-5'), 7.47 (m, 1H, ArH, H-3'), 7.69 (m, 1H, ArH, H-6'), 8.91 (s, 1H, OH). 13 C-NMR (126 MHz, DMSOd 6 ): (δ) 41.1 (CH 2 ), 46.4 (CH 2 ), 50.2 (CH 2 ), 50.4 (CH 2 ), 115.5 (C-2" and C-6"), 118.4 (C-2'),118.5 (C-3" and C-5"), 128.0 (C-5' and C-6'), 130.6 (C-4'), 132.5 (C-3'), 137.9 (C-1'), 143.7 (C-1"), 151.5 (C-4"), 166.…”
Section: General Procedures For the Synthesis Of Compounds 2-35mentioning
confidence: 99%
“…14 These SAR studies also demonstrated that the stereochemistry around the dioxolane region is critical for potent Hh inhibition. [14][15][16] Analogues with the 4R orientation are significantly more active than their 4S counterparts. By contrast, the absolute orientation at the C-2 position is less important.…”
mentioning
confidence: 97%
“…8 ITZ is also a potent inhibitor of Hh signaling in both in vitro and in vivo of Hh-dependent cancer. [12][13][14][15][16] Interestingly, ITZ remains active against several clinically relevant Smo mutants in mouse embryonic fibroblasts (MEFs), suggesting the distinctness from other SMO antagonists. 17,18 Taken together, ITZ represents a promising anticancer agent, that has the ability to address the acquired resistance associated with other Smo antagonists.…”
mentioning
confidence: 99%